A study on the multi-objective optimization method and characteristic analysis of installation locations of submersible mixer for sewage - Tian, Fei; Yang, Chen; Zhang, Erfeng; Sun, Dehua; Shi, Weidong; Chen, Yonghua (Frontiers in Energy Research, 2023)
In order to enhance the performance of submersible mixers in sewage treatment, this study selected installation position parameters of the submersible mixer as design variables, with the aim of improving the average flow velocity and mixing efficiency in the pool. The study employed ISIGHT software, integrated with Creo Parametric 6.0 software and ANSYS Workbench 2020 software, to analyze the factors affecting mean flow velocity and completed a multi-objective optimized design using Non-dominated Sorting Genetic Algorithm (NSGA-II). The results indicated an approximate increase of 0.021 m/s in average flow velocity and an improvement of approximately 0.47% in mixing efficiency compared to pre-optimization values. The effective axial propulsion distance and effective radial diffusion radius were significantly increased by 6.71% and 8.33%, respectively, after optimization. The fluid distribution in the pool became more uniform, and the low-speed zone was greatly reduced, resulting in an enhanced flow state of the fluid in the pool and a strengthened mixing effect. Moreover, the study provides insights into the control of the submersible mixer's installation position to improve the average flow velocity inside the pool. Overall, automatic optimization of submersible mixer installation locations using the ISIGHT software can effectively improve mixing efficiency, overall plant operating efficiency, and economic benefits in sewage treatment plants. The multi-objective optimization platform based on the ISIGHT platform for wastewater treatment mixer installation location can be successfully applied in engineering practice.